2019
DOI: 10.1111/jeb.13528
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of mating types in finite populations: The precarious advantage of being rare

Abstract: Sexually reproducing populations with self‐incompatibility bear the cost of limiting potential mates to individuals of a different type. Rare mating types escape this cost since they are unlikely to encounter incompatible partners, leading to the deterministic prediction of continuous invasion by new mutants and an ever‐increasing number of types. However, rare types are also at an increased risk of being lost by random drift. Calculating the number of mating types that a population can maintain requires consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Stationary distributions are the stochastic equivalents of deterministic fixed points and as such provide a basic description and a starting point for further analysis of the qualitative behavior of a stochastic model, especially in situations where polymorphisms of alleles, coexistence of species, or spatial population distributions are to be expected (e.g., Czuppon & Rogers, 2019;Gaston & He, 2002;Lehmann, 2012;Polansky, 1979;Turelli, 1981).…”
Section: Stationary Distribution Of the Wright-fisher Diffusionmentioning
confidence: 99%
“…Stationary distributions are the stochastic equivalents of deterministic fixed points and as such provide a basic description and a starting point for further analysis of the qualitative behavior of a stochastic model, especially in situations where polymorphisms of alleles, coexistence of species, or spatial population distributions are to be expected (e.g., Czuppon & Rogers, 2019;Gaston & He, 2002;Lehmann, 2012;Polansky, 1979;Turelli, 1981).…”
Section: Stationary Distribution Of the Wright-fisher Diffusionmentioning
confidence: 99%
“…New mating types experience a selective advantage both in terms of increased mating opportunities relative to the two residents and a (shared) increase in the probability of mating with a genetically distinct individual. There is then selection for an ever greater number of mating types, which are only kept bounded by genetic drift (Constable and Kokko, 2018;Czuppon and Rogers, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength of selection for these new mating types decreases as c and σ decrease, and as k increases. The decrease in selection strength in these parameter regimes will lead to higher rates of extinction of mating type alleles when genetic drift is accounted for (Czuppon and Rogers, 2019). This has been previously quantified analytically in the limit of c → ∞ (Constable and Kokko, 2018;Czuppon and Constable, 2019).…”
Section: Deterministic Dynamics For Si Allele Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…the adult population is of finite size). This approach makes our work link with models of stochastic loss of mating types in finite populations [23][24][25][48][49][50], which previously have been built for isogamous systems only. Here we have shown that under anisogamy there is potential for the mating type producing smaller gametes to outcompete a type producing larger gametes.…”
Section: Discussionmentioning
confidence: 99%